TOXOPLASMOSIS IN FELIS CATUS: ETIOLOGY, EPIDEMIOLOGY AND DISEASE - Grandía G., Raiden (2013)
Toxoplasma gondii is the causal agent of toxoplasmosis, a re-emerging and cosmopolitan zoonosis, affecting intermediate and definitive hosts. The domestic cat is the definitive host closer to the human that develops the sexual form of the parasite and it is the producer of oocysts. For this, its presence in the environment is essential in the biologic cycle of T. gondii. Research in cats worldwide is limited principally due by the complexity in the sampling; however, those studies have developed knowledge about taxonomy, morphology, biologic cycle and molecular biology, as well as its geographic distribution, hosts, resistance to environment, transmission patterns, contamination sources and rick factors associated to infection in this species and in other vulnerable species. Besides, studies have been conducted for the understanding of the pathogeny, clinical signs, anatomo-pathological lesions, immunity, diagnosis, and control of this biologic agent.